1995
DOI: 10.1002/jor.1100130412
|View full text |Cite
|
Sign up to set email alerts
|

Changes in innervation of long bones after insertion of an implant: Immunocytochemical study in goats with antibodies to calcitonin gene‐related peptide and B‐50/GAP‐43

Abstract: Sum m ary: In this study, we describe the distribution of fibres th a t co n tain calcitonin g e n e -re la te d p e p tid e in norm al bones and in bones th a t are rem odeling a fter insertion of an im plant. W ith ro u tin e histology and a n ti bodies to calcitonin gen e-related peptide, sm all neural and free-ru n n in g fibres staining positively lo r c alcito nin gene-related p ep tid e w ere found in the p erio steu m , en d o steu m , and cortical bone of the tibia in the goat. In m any cases, th e fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The P13K-AKT pathway, upregulated on SLActive surfaces (in relation to angiogenesis), has also been implicated in neuronal survival and subsequent neural development [77,78] and could have contributed to upregulation of neurogenic genes at these surfaces. Indeed, previous histologic reports have described changes in bone innervation after implant placement (and loading) and the presence of nerve fibers within the peri-implant bone, in animals and humans [79-81]. …”
Section: Resultsmentioning
confidence: 99%
“…The P13K-AKT pathway, upregulated on SLActive surfaces (in relation to angiogenesis), has also been implicated in neuronal survival and subsequent neural development [77,78] and could have contributed to upregulation of neurogenic genes at these surfaces. Indeed, previous histologic reports have described changes in bone innervation after implant placement (and loading) and the presence of nerve fibers within the peri-implant bone, in animals and humans [79-81]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Buma et al (1995) have observed that the insertion of a medullary implant into the goat tibia produces a region of necrotic endosteal bone that is no longer viable. At 6 weeks, however, a repair phase is initiated that ultimately revascularizes and remodels the necrotic endosteal bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…33 Manipulation of endosteum in patients with resurfacing is minimal, and there is no continued stretching of endosteum after surgery. It is possible that manipulation of medullary canal during reaming and broaching for THA leads to some increase in pain.…”
Section: Discussionmentioning
confidence: 99%